Routes to increase performance for antimony selenide solar cells using inorganic hole transport layers - Campbell, Stephen; Phillips, Laurie J.; Major, Jonathan D.; Hutter, Oliver S.; Voyce, Ryan; Qu, Yongtao; Beattie, Neil S.; Zoppi, Guillaume; Barrioz, Vincent (Frontiers in Chemistry, 2022)
Simple compound antimony selenide (Sb2Se3) is a promising emergent light absorber for photovoltaic applications benefiting from its outstanding photoelectric properties. Antimony selenide thin film solar cells however, are limited by low open circuit voltage due to carrier recombination at the metallic back contact interface. In this work, solar cell capacitance simulator (SCAPS) is used to interpret the effect of hole transport layers (HTL), i.e., transition metal oxides NiO and MoOx thin films on Sb2Se3 device characteristics. This reveals the critical role of NiO and MoOx in altering the energy band alignment and increasing device performance by the introduction of a high energy barrier to electrons at the rear absorber/metal interface. Close-space sublimation (CSS) and thermal evaporation (TE) techniques are applied to deposit Sb2Se3 layers in both substrate and superstrate thin film solar cells with NiO and MoOx HTLs incorporated into the device structure. The effect of the HTLs on Sb2Se3 crystallinity and solar cell performance is comprehensively studied. In superstrate device configuration, CSS-based Sb2Se3 solar cells with NiO HTL showed average improvements in open circuit voltage, short circuit current density and power conversion efficiency of 12%, 41%, and 42%, respectively, over the standard devices. Similarly, using a NiO HTL in TE-based Sb2Se3 devices improved open circuit voltage, short circuit current density and power conversion efficiency by 39%, 68%, and 92%, respectively.